Application of the Principles of Electoral District Arrangement and Islamic Political Principles in the Formation of Electoral Districts for the DPRD of North Sumatra Province for the 2024 Election - Agussalam, Agussalam; Katimin, Katimin; Harahap, Elly Warnisyah (PERSPEKTIF, 2024)
This research discusses the application of electoral district structuring principles and Islamic political principles in the formation of North Sumatra Province DPRD Electoral Districts in the 2024 Election. Using qualitative research methods, normative approaches, and Miles and Huberman's interactive data analysis model. This research investigates the extent to which these principles are reflected in the determination of electoral districts. The results of the research show that the principle of equal vote value and the principle of proportionality has not been fully accommodated in the Determination of Electoral Districts for the DPRD of North Sumatra Province for the 2024 Election, based on the Principles of Electoral District Arrangement. According to the perspective of Islamic political principles such as obedience, justice, and equality (al-musawah), they cannot be fully applied in determining electoral districts. Further analysis reveals that the main factor causing the non-implementation of these principles is political influence in determining electoral districts for the DPR and Provincial DPRD in the 2024 Election. This research makes an important contribution to understanding the challenges and obstacles faced in realizing the democratic and political principles of Islam in the context of regional elections. The implications of these findings emphasize the need for reform to increase the value of voting representation and proportionality, in line with Islamic political principles. Practical recommendations involve policy reform and tighter oversight to reduce detrimental political influences. It is hoped that these steps will improve the implementation of these principles in future regional election systems.